How Was Your Otology Training? A Survey of Recent Otolaryngology Residents. Issue 10 (December 2017) - Montague, Phillip; Bennett, Donald; Kellermeyer, Brian
Abstract : Objective: To survey graduating residents or recent graduates of otolaryngology residency programs to evaluate their Otology/Neurotology (ON) experience in residency and discern if they had received adequate training in time to decide whether to pursue a fellowship in Otology or Neurotology. Study Design: Internet-based survey. Methods: A survey was distributed to all US otolaryngology residency programs to distribute to 5th year residents and recent graduates in last 4 years. The survey assessed satisfaction in ON experience, presence of ON fellows, adequacy of experience to decide on ON fellowship, post-graduate year (PGY) year at which residents observed, performed, and proficiently performed five procedures (tympanoplasty, mastoidectomy, ossiculoplasty, stapedectomy, and cochlear implant), and plan for performing these surgeries in practice. Results: 89/106 (84%) of respondents felt they had adequate training in Otology in time to decide whether or not to pursue a fellowship and were found to observe and perform surgeries significantly earlier in training by PGY including: mastoidectomy (observed PGY 1.9 versus PGY 2.3, performed PGY 2.9 versus PGY 3.5), ossiculoplasty (observed 2.1 versus 3.0, performed 3.6 versus 4.3), stapedectomy (observed 2.3 versus 3.0, performed 3.9 versus 4.5), and cochlear implant (observed 2.1 versus 2.8, performed 3.4 versus 4.1) all p  < 0.05. There were 19/106 (17.9%) respondents who came from programs with fellowships and 78.9% thought fellows were beneficial to their ON experience. Conclusions: Early exposure to ON surgeries may aid in residents' decision to pursue a fellowship in ON. The presence of fellows appears to facilitate residents' ON experience. Abstract : Supplemental Digital Content is available in the text